Images of bodies in mass and social media and body dissatisfaction: The role of internalization and self-discrepancy - Möri, Michelle; Mongillo, Federica; Fahr, Andreas (Frontiers in Psychology, 2022)
The study examines the influence on body dissatisfaction of viewed images of bodies transmitted over mass media and social media, as mediated by the internalization of body ideals through media and self-discrepancy (the difference between the perceived actual self and the perceived ideal self). In this study, the images of bodies individuals view in their everyday media diet are estimated using a newly developed pictorial scale for women (thinness) and men (muscularity). For participants, the perceived body image is formed through mass media (magazines, TV) and social media (Facebook, YouTube, Instagram, Snapchat). The self-discrepancy theory is then used to explain the effect of images of bodies in the media on the internalization of these body ideals and body dissatisfaction. Results show that Facebook and YouTube shape body ideals perceived to be prevalent in the media, negatively influencing internalization and self-discrepancy. Self-discrepancy, in turn, increases body dissatisfaction. However, for males, the perceived body ideals in the media did not affect body dissatisfaction, internalization, or self-discrepancy. These results emphasize the importance of combining and comparing mass and social media and differentiating between female and male concerns regarding body image.